Study on the Influence of Modified Design on the Dynamic Characteristics of the Helical Gear System - Wang Ruoyi; Yang Jianwei; Wang Jinhai (Jixie chuandong)
In order to study the dynamic characteristics of helical gears with different modified designs, a pair of standard gears and modified gears are taken as comparative experimental objects, and the dynamics model of a modified helical gear system is established based on Lagrange dynamics. An analytical method is used to solve the time-varying meshing stiffness of a modified helical gear, and the influence of different modification coefficients on the meshing stiffness is analyzed. By combining the time-varying meshing stiffness of helical gears with the dynamic model, the influence of different modified designs on the dynamic characteristics of the helical gear system is analyzed. The results show that the positive drive reduces the time-varying meshing stiffness, thereby reducing the meshing force, and the negative drive increases the time-varying meshing stiffness, thereby increasing the meshing force. The results can provide a reference basis for designing and optimizing the subsequent helical gear transmission.